Brief Report: Inflammatory Colonic Innate Lymphoid Cells Are Increased During Untreated HIV-1 Infection and Associated With Markers of Gut Dysbiosis and Mucosal Immune Activation. (1st December 2017) - Dillon, Stephanie M.; Castleman, Moriah J.; Frank, Daniel N.; Austin, Gregory L.; Gianella, Sara; Cogswell, Andrew C.; Landay, Alan L.; Barker, Edward; Wilson, Cara C.
Abstract : Background: HIV-1 infection is associated with intestinal inflammation, changes in the enteric microbiota (dysbiosis), and intestinal epithelial cell damage. NKp44 + innate lymphoid cells (ILCs) play an important role in epithelial barrier maintenance through the production of interleukin (IL)-22 but also display functional plasticity and can produce inflammatory cytokines [eg, interferon gamma (IFNγ)] in response to cytokine milieu and stimulatory signals. The objective of this pilot study was to enumerate frequencies of IL-22 and IFNγ-expressing colonic NKp44 + ILCs during untreated, chronic HIV-1 infection. Setting: A cross-sectional study was performed to compare numbers of cytokine-expressing ILCs in colonic biopsies of untreated, chronic HIV-1 infected (n = 22), and uninfected (n = 10) study participants. Associations between cytokine + ILC and previously established measures of virological, immunological, and microbiome indices were analyzed. Methods: Multicolor flow cytometry was used to measure the absolute number of colonic CD3 − NKp44 ± CD56 ± ILCs expressing IL-22 or IFNγ after in vitro mitogenic stimulation. Results: Numbers of colonic NKp44 + ILCs that expressed IFNγ were significantly higher in HIV-1 infected versus uninfected persons and positively correlated with relative abundances of dysbiotic bacterial species in the Xanthomonadaceae and Prevotellaceae bacterial families and with colonic myeloid dendritic cell and T-cell activation. Conclusion: Higher numbers of inflammatory colonic ILCs during untreated chronic HIV-1 infection that associated with dysbiosis and colonic myeloid dendritic cell and T-cell activation suggest that inflammatory ILCs may contribute to gut mucosal inflammation and epithelial barrier breakdown, important features of HIV-1 mucosal pathogenesis. Abstract : Supplemental Digital Content is Available in the Text.